Design and Initial Implementation of a Distributed XML Database - Pagnamenta, Francesco (Trinity College Dublin. Department of Computer Science, 2005)
Techniques for distributed relational database systems have been well researched and developed. This is unsurprising given that the relational database model itself has been in development since the early 1970s. In recent years, XML has emerged as an excellent simple format for structuring and exchanging data, and the problem of using relational databases or specially designed ?native? XML databases for managing XML data has also been gradually addressed. However, although some research has gone into providing techniques for different parts of the distributed XML database problem, very little research has gone into trying to put these techniques together in order to create a distributed XML database platform. This project investigates the design issues that need to be addressed for the implementation of such a distributed XML database platform. It surveys the state-ofthe- art of XML-based technologies that can be adopted and mechanisms that can be used. The dissertation proposes a layered architecture with a data access infrastructure at the bottom layer able to integrate different types of databases supporting XML. Acting on the top of the access infrastructure, three main functional components are proposed: a distributed transaction manager, a distributed query processor, and a distributed schema manager. Additionally, support for distributed transactions has been designed and implemented. The project includes an initial implementation of the system. The evaluation of the implementation shows that an XML-based multidatabase system is conceivable. However, it emerged that some techniques required for achieving an efficient XML distributed database have to be enhanced.
Keywords: Computer Science